The temperature-controlled growth of In2O3 nanowires, nanotowers and ultra-long layered nanorods - Singh, Nandan (2013)
Indium oxide (In2O3) nanowires (with diameters of 25–90 nm and lengths of 10–50 µm), nanotowers (with diameters 100–150 nm and lengths below 10 µm) and long layered nanorods (with diameters of 200–400 nm and lengths of 20–50 µm) are grown through carbothermal reduction of In2O3 powder by varying the source temperature in a CVD horizontal furnace. At 875 °C source temperature, In2O3 nanowires were formed by a VLS (vapor–liquid–solid) mechanism. The growth is changed to VS (vapor–solid)-initiated growth on the substrate surface when the source temperature is raised to 950 °C due to high saturation vapor pressure. Meanwhile, alternate VLS–VS grown nanotowers can be obtained at the bottom of the substrates. Growth of one-dimensional nanostructures with different structures and variation in growth mechanism from a single precursor with the confinement of vapor pressure enables the diversity of In2O3 nanostructure synthesis. The morphologies and crystalline structures are characterized by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and high-resolution transmission electron microscopy (HRTEM). The growth mechanisms of these structures are discussed.